A systems study on the operations department of ABC Foods, Inc. - De Guzman, Dennis A. (Animo Repository, 2008)
ABC FOODS, INC., through 24 years of service, has obtained excellence on product quality and continuously strives to maintain its technical expertise in fruit purees processing and new product development. Its mission is to be able to process and market all natural, safe and healthy fruit purees to meet average customer demands. It envisions itself to be the top food conglomerate engaged in the productions and distributions of industrial food products, as well as production, distribution and licensing of internationally known brands of ready to consume food products. The production system of fruit puree of the company is experiencing unwanted raw material cost due to raw fruit wastage and low production yield during 2007, which resulted in a net cost of Php5,649,543.88. Using Cause-and-Effect and Pareto, the root causes that were proven to be contributing 95.63% to the high raw material wastage and low production yield are occurrence of machine breakdown, poor ripening procedure, and improper trimming tools used. The solutions were proposed to address the significant causes of the problem include the creations of a preventive maintenance policy for machines, application of non-toxic chemical in speeding/delaying fruit ripening, purchasing of ergonomic trimming tools, and implementation of 100% incoming inspection for all fruits. Using simple Cost-Benefit Analysis, the comparison between the total cost of implementation of proposed solutions from the total expected annual savings resulted in a total net benefit of Php4,643,243.73. The solutions are found to be feasible and ready to be implemented within a span of three months.